Gasping for air: soccer players` passing behavior at high-altitude - Tovar, J. (Journal of Quantitative Analysis in Sports, 2014)
A number of soccer officials have long debated whether to ban soccer games played at high altitude above sea level. This paper explores soccer player`s passing behavior when playing at high elevations using Copa Libertadores data. For this, I propose a range of direct indicators when playing at high altitude: the number of total passes, the number of passes in the opposition`s half, and the number of successful passes. I also review the effects on the percentage of successful passes and the percentage of successful passes in the opponents` half of the field. Player`s passing abilities are compared for games played away above 2500 m (8202 feet) vis-à-vis those held below that threshold. The results show that the percentage of successful passes rises by about 5.6 percentage points, mostly driven by each player`s behavior in his own half. Following earlier findings by Romer (2006) and Palacios-Huerta (2014), who state that players behave conservatively under certain circumstances, I argue that players` have prior believes about the effects of playing at high altitude and consequently their risk aversion to lose the ball increases.